If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12/5+x=2
We move all terms to the left:
12/5+x-(2)=0
determiningTheFunctionDomain x-2+12/5=0
We multiply all the terms by the denominator
x*5+12-2*5=0
We add all the numbers together, and all the variables
x*5+2=0
Wy multiply elements
5x+2=0
We move all terms containing x to the left, all other terms to the right
5x=-2
x=-2/5
x=-2/5
| 12x/8+4x=32 | | 8m+23=33 | | 0=4.5+9.8t | | √(x^2-5х)=√(-3-х) | | 8x+9=6+7x | | 2c-5=c+3 | | x+2x+7=87 | | x/5/12=4/15 | | X(6x+7)=26 | | 12x+8=24+6x | | 2x^2+2x+4=1252 | | x+2/3=-7/8 | | (2x^2)+(2x)+4=1252 | | 3x/12=27x/24 | | 9x/4=8x/20 | | 8(c+2)c=9 | | (2x–5)/(x+3)=0 | | 2/4+3x=90 | | 2^n=1.25 | | -3x+(x+1)^2=3 | | 1,5-0,2V(x)=0,6 | | 3x/5+5=25 | | (x+1)^2-3(x+1)=0 | | 1,5-0,2√(x)=0,6 | | 2x×5=x-3 | | 1,5-0,2√x=0,6 | | 2y/2+3=12 | | (x+1)(x+1)-3(x+1)=0 | | x²-x-1=0 | | 2+x=7/4 | | 9b-2=2(3b+5 | | 6(2y+3)-6(y+1)=29 |